Project of Ecobricks in Social Studies for The Environment-Caring Character of Students - Azizah, Nur Azizah; Supriatna, Nana; Sundawa, Dadang (Jurnal Paedagogy, 2023)
This study aims to analyze the increased caring character of the student environment that acquires learning by using the project-based learning model of Ecobricks in social sciences learning. The research methods used quasi-experimental with nonequivalent pretest and posttest control group designs. The instruments used in the research were the questionnaire pretest and posttest. The student population of class VII 1 as a control class and class VII 5 as an experimental class was determined through descriptive analysis assisted by descriptive statistics to describe the initial and final characters of the experimental and control class students. Research results showed that using the project-based learning model of Ecobricks in Social Sciences lessons to develop the values of creativity and innovation can better enhance the character of caring for the studentâ€™s environment than learning by using multi-design PowerPoint media. Based on pretest and posttest results, the increased care character of the student environment in the experimental class is enhanced to the â€œmiddleâ€ category.Â